Evaluation of Immunomodulatory Effects of Silkworm (Bombyxmori L.) Cocoon Extracts on Methylprednisolone Induced Rats - M, Soumya; Reddy, Harinatha; G, Nageswari; Venkatappa (International Journal of Scientific Research in Biological Sciences, 2018)
The present study aimed to evaluate the immunomodulatory effects of cocoon extracts of Silkworm on methylprednisolone drug induced immunosuppression in rats. Silkworm cocoons were collected and extracts were prepared. A total of 24 Wistar Albino rats divided into four groups were used in the study. Group-I rats were treated with distilled water. Group-II rats received Methyl prednisolone (20mg/kg), Group-III rats given cocoon extract of Silkworm (300mg/kg) + Methyl prednisolone(20mg/kg) and Group-IV received cocoon extract of Silkworm (500 mg/kg) + Methyl prednisolone (20mg/kg). Physical and immunological parameters were measured on 6th and 12th day. At the end of study rats were sacrificed under anesthesia. Spleen was collected , weighed and examined for histopathology. The results and findings of the study suggest the immune enhancement activity of cocoon extacts of Silkworm on methylprednisolone induced immunosuppression.